A Painful Case of Debilitating Cutaneous Psoriasis - Khurram Bilal Tariq; Farhangi Arezo; Rana Fauzia (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2014)
Psoriasis is an immune mediated, chronic infl ammatory, incurable condition of the skin that aff ects 2-3% of the population globally. It is associated with red, thick, scaly lesions [1], is more common in patients on higher latitudes, in Caucasians and may manifest itself with an underlying arthropathy. Psoriasis has a spectrum of presentations ranging from localized, mild disease to involvement of more than 90% of the body's surface called erythrodermic form [2]. In as many as 4% of the patients with psoriatic the fi rst sign of disease involves changes to the nail, however, these nail changes are seen in about half patients at some point in the course of the disease. Arthropathy, specifi cally, Psoriatic arthritis is also seen in about 5-10% of this patient population.